Speculations of Immunotherapy in COVID-19 Patients with Practical Applications During Childhood and Pregnancy - Al-Momen, Hayder; Jasim, Shaymaa Kadhim; Al-Ameri, Laith Thamer (AL-Kindy College Medical Journal, 2020)
The rapid spread of novel coronavirus disease(COVID19) throughout the world without availablespecific treatment or vaccine necessitates alternativeoptions to contain the disease. Historically, childrenand pregnant women were considered high-riskpopulation of infectious diseases but rarely have beenspotlighted nowadays in the regular COVID-19updates, may be due to low global rates of incidence,morbidity, and mortality. However, complications didoccur in these subjects affected by COVID-19. Weaimed to explore the latest updates ofimmunotherapeutic perspectives of COVID-19patients in general population and some added detailsregarding pediatric and obstetrical practice.Immune system boosting strategy is one of therecently emerging issues allowing the body defensemechanism to produce virus-neutralizing antibodies tocounteract the viral impacts on multiple organdamage. Measles vaccination (which is universallyused for children in many countries, butcontraindicated during pregnancy) could urge thebody to produce these antibodies which may applytheir effects through cross-reactivity of measlesvaccine and COVID-19 antigenic proteins. Inaddition, intravenous immunoglobulin andconvalescent plasma could have such neutralizingantibody effect leading to clinical improvement andviral elimination. Pediatric and obstetrical experiencehas appeared in previous publications.Human monoclonal antibodies are the futurepromising approach to treat and prevent COVID-19with the use of tocilizumab in recent studies. Pediatricdata are still in progress while no pregnancy ongoingtrials are planned up to date.The better understanding of the host antiviral responsemay pave the way to develop immunotherapeuticplans against COVID-19 in the near upcoming days.